Analisis Swot Umkm Rumah Makan Chinese Food Dua Putra Di Bekasi - Ridwan Irawan, Muhammad; Daspar Daspar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, including in the culinary sector. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) of the Seafood Dua Putra restaurant in Bekasi. The research approach used is descriptive qualitative with a case study method. Data were collected through interviews, observation, and documentation. The analysis results indicate that this MSME possesses key strengths in authentic taste, strategic location, and affordable pricing. However, it still faces challenges such as limited capital, undertrained human resources, and a lack of digital marketing implementation. The recommended development strategies include expanding digital marketing, collaborating with food delivery services, and improving internal management quality.